The Worrywart's Companion : Twenty-one Ways to Soothe Yourself and Worry Smart - Potter, Beverly A. (New York McGraw-Hill, 2009)
Do you like to lie awake at night agonizing over things that could happen? Do you automatically expect the worst? Have you worried obsessively about things only to have everything turn out okay? Instead of worrying yourself sick, let the Worrywart's Companion show you how to worry smart and soothe yourself so that you can think more clearly, deal with the worry at hand, and then let it go.
Keywords: Worry